Spontaneous regression in advanced squamous cell lung carcinoma - Park, Yeon Hee; Park, Bo Mi; Park, Se Yeon; Choi, Jae Woo; Kim, Sun Young; Kim, Ju Ock; Jung, Sung Soo; Park, Hee Sun; Moon, Jae Young; Lee, Jeong Eun (Journal of Thoracic Disease, 2016)
Spontaneous regression of malignant tumors is rare especially of lung tumor and biological mechanism of such remission has not been addressed. We report the case of a 79-year-old Korean patient with non-small cell lung cancer, squamous cell cancer with a right hilar tumor and multiple lymph nodes, lung to lung metastasis that spontaneously regressed without any therapies. He has sustained partial remission state for one year and eight months after the first histological diagnosis.